A Case Study on Preservation Conditions and Influencing Factors of Shale Gas in the Lower Paleozoic Niutitang Formation, Western Hubei and Hunan, Middle Yangtze Region, China - Shengling Jiang; Qinghua Zhou; Yanju Li; Rili Yang (Geofluids)
The Niutitang Formation of the lower Cambrian (Є1n) is a target reservoir of shale gas widely developed in China’s Middle-Upper Yangtze region, with the characteristics of being widely distributed, having a big thickness and highly organic carbon abundance. However, the exploration and research degree are relatively low. Based on extensive core sample, experimental test results, drilling, and field outcrop surveying, the shale gas generation capacity, gas content, and gas composition are discussed. The preservation conditions of shale gas are then systematically analyzed from the aspects of tectonic movement, fault development, structural style, and thermal evolution degree. The results show that the organic-rich shale with a thickness ranging from 40 to 150 m developed in the mid-lower part of the Є1n Formation, with the TOC content values ranging from 0.4% to 14.64%. While it has unfavorable characteristics of a high thermal evolution, with Ro values ranging from 1.92% to 5.74%, a low gas content and a high nitrogen content (70% wells). The Є1n shale gas has complex preservation conditions. The Є1n Formation has good roof-to-floor conditions, but after the main gas generating peak of the Є1n shale during the Jurassic–Cretaceous, the most intensive tectonic activity of the Yanshan movement resulted in poor preservation conditions (faults developed and cap rock fractured). The huge faults extended to the surface are formed due to tectonic movement in an extensional environment, and the structural style and development are the main factors affecting the preservation conditions of the Є1n shale gas. Additionally, the high thermal evolution of the Є1n shales also has a certain impact on the preservation conditions. Therefore, the stable area far from large faults (>2.0 km), with weak local tectonic activity and tectonic deformation, is the favorable area for shale gas preservation in the Є1n Formation.